PEMBERIAN AROMATERAPI MINYAK PEPPERMINT SECARA INHALASI BERPENGARUH TERHADAP PENURUNAN MUAL MUNTAH PADA IBU HAMIL DI PMB LINDA SILALAHI PANCUR BATU TAHUN 2019 - Lubis, Rismahara; Evita, Sonya; Siregar, Yusniar (Poltekkes Kemenkes Medan, 2019)
Feelings of nausea and vomiting are one of the discomforts that are often found in pregnancy and which usually occur early in pregnancy. The handling of vomiting and nausea can be done through non-pharmacological therapy in the form of peppermint oil inhaled aromatherapy that is noninstructive, non-invasive, inexpensive, effective and has no side effects. This study aims to determine the effect of peppermint oil inhaled aromatherapy on decreasing the nausea and vomiting in pregnant women at the private clinic of Linda Silalahi Pancur Batu. This research is a pre-experimental study designed with one group pretest posttest designs examining 15 pregnant women as samples obtained through purposive sampling techniques. Then the data were analyzed by the Wilcoxon Sign Rank Test and based on the results of the study it was found that before the inhalation of the peppermint oil aromatherapy, majority of the pregnant women experienced moderate nausea, 12 people (80%), but after the aromatherapy majority of pregnant women did not experience nausea vomiting, 12 people (80%). It was also found that differences in the mean scores of nausea and vomiting of pregnant women before and after inhalation of peppermint oil aromatherapy were 6.13. Through the Wilcoxon Sign Rank Test obtained p value of 0.001, which means that there is an effect aromatherapy to decrease nausea and vomiting in pregnant women at private clinic of Linda Silalahi Pancur Batu. Pregnant women who experience nausea and vomiting can use peppermint oil inhaled aromatherapy to reduce the use of pharmacological therapy.